2021
DOI: 10.3390/e23050588
|View full text |Cite
|
Sign up to set email alerts
|

Training Data Selection and Optimal Sensor Placement for Deep-Learning-Based Sparse Inertial Sensor Human Posture Reconstruction

Abstract: Although commercial motion-capture systems have been widely used in various applications, the complex setup limits their application scenarios for ordinary consumers. To overcome the drawbacks of wearability, human posture reconstruction based on a few wearable sensors have been actively studied in recent years. In this paper, we propose a deep-learning-based sparse inertial sensor human posture reconstruction method. This method uses bidirectional recurrent neural network (Bi-RNN) to build an a priori model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…They have replaced the RNNs which suffer from the vanishing gradient problem during the training and include forget gates to quickly adapt to the new changes of data. These DNNs can use just the information of accelerometers and the orientation of a set of body segments to estimate the whole-body posture [29] or fuse the information of specific force with the turn rate to estimate the joint angles [53], [69], [86], [103]. A less common approach includes the fusion of gyroscopes and magnetometers to estimate the joint angles [155].…”
Section: Adopted Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have replaced the RNNs which suffer from the vanishing gradient problem during the training and include forget gates to quickly adapt to the new changes of data. These DNNs can use just the information of accelerometers and the orientation of a set of body segments to estimate the whole-body posture [29] or fuse the information of specific force with the turn rate to estimate the joint angles [53], [69], [86], [103]. A less common approach includes the fusion of gyroscopes and magnetometers to estimate the joint angles [155].…”
Section: Adopted Algorithmsmentioning
confidence: 99%
“…the joint or segment orientation or location. In this review, we found 26 works that use reference data, that can be obtained from a stereophotogrammetric system (17/26) [21], [27], [34], [49], [53], [54], [56], [58], [68], [69], [86], [90], [91], [103], [111], [114], [115], electro-goniometer and encoders (2/26) [71], [84] or inertial sensors (7/26) [29], [100], [109], [134], [147], [148], [155]. Fig.…”
Section: Adopted Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…W EARABLE lower-limb joint angle estimation using a reduced inertial measurement unit (IMU) sensor set facilitates the rapid and cost-effective assessment of sports injury risk [1]- [5], motion capture [6]- [9], and improvement of motion techniques [1], [10], [11]. The IMU is a commonly used, lightweight, and affordable sensor that is often integrated with machine learning models to enable kinematic estimation [6], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the quality of reconstruction also emerged as a new criterion for feature selection [4][5][6]. Regardless of whether we observe this problem in terms of sensor (site) selection or optimal sensor placement, we can find a number of proposed solution [7][8][9][10][11][12][13]. This is even more true when we consider the different feature selection algorithms available (e.g., [14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%